Improvements in the micropropagation of the olive tree (Olea europaea L.) - Silva, Daniel Fernandes da (2017)
The olive tree is a Mediterranean species of great importance whose your history is confused with that of ancient civilizations. Known for the consumption of table olives and olive oil, the cultivation of olive trees still presents some obstacles to be resolved, among them propagation problems, since among the hundreds of olive cultivars it is not possible to establish a standard for propagation due to the differentiated behavior between them. Micropropagation presents advantages in relation to cutting and grafting, proposing itself as an interesting possibility, although it still has a high cost due to the demand of zeatin and also low multiplication rate caused by the strong apical dominance, problems that currently remain the focus of research as challenges to be overcome. Knowing this situation, the objective of this study was to evaluate the effect of neem oil insertion on in vitro multiplication of olive cultivar Moraiolo and also to study the interaction of factors which influencing rooting through the in vitro rooting of regenerated shoots of the same cultivar. Two studies were carried out: in the first study four concentrations of neem oil (0, 0.1, 0.5 and 1 ml L -1 ) were added to the OM culture medium, being the regenerated explants cultivated by three successive subcultures in the same conditions to prove the results. In the second study three experiments were established: the experiment 1 aimed to evaluate the interaction between the concentration of salts of the culture medium, the concentration of IBA and the performance of dark induction in the explants; the experiment two analyzed the use of AIB, the darkening of the rooting medium and the induction of explants with light absence; and experiment 3 sought to reduce the time and cost of micropropagated olive seedlings by in vitro substrate rooting similar to that used in the acclimatization of micropropagated olive seedlings, together with the induction of explants to rooting. We concluded that the addition of 0.1 ml L -1 of neem oil allows to obtain olive explants with greater vigor and quality. It is also concluded that the ideal concentration of AIB for rooting of olive explants cultivar Moraiolo is 2 mg L -1 and the induction of explants with 72 hours of dark allied to 2 mg L -1 of IBA improves the quality of the roots formed. The OM medium with half of the salt concentration increases the mass of the roots formed and is sufficient for the rooting of Moraiolo olive explants. Darkening of the culture medium with 150 mg L -1 of Brillant Black ® increases the number of roots formed and the substrate composed of turf and sand in the ratio 3:1 (v:v) was not efficient for direct in vitro rooting.